Long noncoding RNA MALAT1 inhibits the apoptosis and autophagy of hepatocellular carcinoma cell by targeting the microRNA-146a/PI3K/Akt/mTOR axis - Peng, Ningfu; He, Jingrong; Li, Jindu; Huang, Hao; Huang, Weiqiao; Liao, Yingyang; Zhu, Shaoliang (Cancer cell international, 2020)
Increased long noncoding RNA (lncRNA) expression is characteristic to hepatocellular carcinoma (HCC) and several other neoplasms. The present study aimed to identify the mechanism underlying modulation of HCC development by the lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1). Quantitative real-time polymerase chain reaction was used to determine MALAT1 and microRNA (miR)-146a expression in HCC tissues and cell lines. Western blotting was performed to measure PI3K, Akt, and mTOR levels. Dual-luciferase reporter assay was used to validate the direct targeting and negative regulatory interaction between miR-146a and MALAT1. Cell viability, proliferation, and apoptosis were analyzed using an 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay, colony formation assay, and flow cytometry, respectively; autophagy was detected based on LC3B expression. MALAT1 expression was higher in HCC tissues than in normal tissues. MALAT1 upregulation promoted HCC cell proliferation, whereas MALAT1 downregulation promoted HCC apoptosis and autophagy. Moreover, effects of MALAT1 downregulation on HCC cells were abolished by miR-146a inhibition. miR-146a directly targeted the 3'-untranslated region of , and PI3K protein level was clearly decreased upon miR-146a mimic transfection. MALAT1 may modulate HCC cell proliferation, apoptosis, and autophagy via sponging miR-146a, which regulates HCC progression.